to solve the system of equations below, Zach isolated x^2 in the first equation and then substituted it into the second equation. What was the resulting equation. (x^2 y^2=25; (x^2/15-y^2/9=1 A.x^2/16-y^2-25/9=1 B.x^2/16-25-y^2/9=1 C.25-y^2/16-y^2/9=1 D.y^2-25/16-y^2/9=1

Respuesta :

Answer:

25-y²/15 - y²/9 = 1

Step-by-step explanation:

Given the equations x^2 + y^2=25 ...1 and x^2/15-y^2/9=1,.. 2 to solve the systam of equation we will make  x^2 the subject of the formula from the first equation and substitute it into the second equation as shown;

Fom 1; x² = 25-y²... 3

Substituting equation 3 into 2 to get the resulting equation will give;

x²/15-y²/9=1

25-y²/15 - y²/9 = 1

The final expression gives the required equation.

Answer:

(25-y^(2))/(16) - (y^(2))/(9) =1

Step-by-step explanation:

Just took the test